PENGARUH MODEL PEMBELAJARAN KOOPERATIF TGT TERHADAP HASIL BELAJAR IPAS SISWA DI KELAS IV SD - Martina Estepania Hinal Siahaan; Regina Sipayung; Darinda Sofia Tanjung; Frikson Jony Purba; Heka Maya Sari Br Sembiring (Universitas Negeri Medan, 2025)
This study aims to determine the effect of the Teams Games Tournament cooperative learning model on student learning outcomes in IPAS (Integrated Science) in grade IV at Dharma Wanita Pertiwi Elementary School. The background of this study stems from the initial evaluation results which showed that most students had not achieved the minimum competency standard, with 74.19% of students falling into the “Needs Improvement” category. The TGT model was chosen because it integrates group cooperation, educational games, and academic competition that stimulate motivation, active participation, and in-depth understanding of concepts. This study used an experimental method with a one-group pretest-posttest design. The research sample consisted of all 31 fourth-grade students, selected using total sampling technique. The research instruments included learning outcome tests and student response questionnaires. Data analysis was conducted using the N-Gain test to measure learning outcome improvement and the t-test to examine the significance of the difference between pretest and posttest scores. The results showed an average N-Gain of 0.56, which falls into the moderate category (0.3≤ < 0.7), indicating a significant improvement in learning outcomes. The t-test produced a t-count of 6.116, which was greater than the t-table of 1.696 (α = 0.05), so Ha was accepted and Ho was rejected. These findings prove that the TGT cooperative learning model has a positive and significant effect on IPAS learning outcomes, while also increasing motivation, activity, cooperation skills, and a more enjoyable learning atmosphere in the classroom.